COVID-19-Related Brain Injury: The Potential Role of Ferroptosis - Zhang R; Sun C; Chen X; Han Y; Zang W; Jiang C; Wang J; Wang J (Dove Medical Press, 2022)
Ruoyu Zhang,1,* Chen Sun,1,* Xuemei Chen,1 Yunze Han,1 Weidong Zang,1 Chao Jiang,2 Junmin Wang,1 Jian Wang1 1Department of Human Anatomy, School of Basic Medical Sciences, Zhengzhou University, Zhengzhou, Henan Province, 450001, People's Republic of China; 2Department of Neurology, The Fifth Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan Province, 450052, People's Republic of China*These authors contributed equally to this workCorrespondence: Jian Wang; Junmin Wang, Department of Anatomy, School of Basic Medical Sciences, Zhengzhou University, Zhengzhou, Henan, People's Republic of China, Email jianwang2020@outlook.com; wangjunmin@zzu.edu.cnAbstract: The COVID-19 pandemic has caused devastating loss of life and a healthcare crisis worldwide. SARS-CoV-2 is the causative pathogen of COVID-19 and is transmitted mainly through the respiratory tract, where the virus infects host cells by binding to the ACE2 receptor. SARS-CoV-2 infection is associated with acute pneumonia, but neuropsychiatric symptoms and different brain injuries are also present. The possible routes by which SARS-CoV-2 invades the brain are unclear, as are the mechanisms underlying brain injuries with the resultant neuropsychiatric symptoms in patients with COVID-19. Ferroptosis is a unique iron-dependent form of non-apoptotic cell death, characterized by lipid peroxidation with high levels of glutathione consumption. Ferroptosis plays a primary role in various acute and chronic brain diseases, but to date, ferroptosis in COVID-19-related brain injuries has not been explored. This review discusses the mechanisms of ferroptosis and recent evidence suggesting a potential pathogenic role for ferroptosis in COVID-19-related brain injury. Furthermore, the possible routes through which SARS-CoV-2 could invade the brain are also discussed. Discoveries in these areas will open possibilities for treatment strategies to prevent or reduce brain-related complications of COVID-19.Keywords: brain injuries, cell death, COVID-19, ferroptosis, iron, neuropsychiatric symptoms